Investigation of a compact unglazed solar thermal façade for building integration - SHEN, JINGCHUN (2017)
In order to achieve the global carbon emission reduction target, it is expected to become essential for higher fraction of locally available renewable energy sources in energy mix, other than significant reduction of fossil energy consumption. Solar energy is one of the most promising renewable sources locally with various building applications. In addition, the Solar Thermal Facade (STF) system demonstrates a real sense of building integration that can be a potential solution towards energy efficiency improvement and operational cost reduction in contemporary built environment.